Analysis on Deck Ship Conversion SPOB to LCT 234 GT Using Finite Element Method - Amalia Ika Wulandari; Andi Mursid Nugraha Arifuddin; Nurul Huda (Institut Teknologi Sepuluh Nopember, 2022)
Landing Craft Tank (LCT) is a sea transportation that serves to carry various types of cargo and heavy mining equipment and has a large size. In shipbuilding, the construction structure on the ship is not only designed to be able to accept the load from the cargo being transported but also must be able to withstand external loads caused by waves. With the modification of the Self-Propelled Oil Barge (SPOB) ship into a Landing Craft Tank (LCT), the calculation and planning process on the deck structure of the Landing Craft Tank (LCT) ship really needs to pay attention to the stress and strain strength in order to meet the safety factors that have been set in accordance with the applicable rules. This study aims to determine the maximum allowable stress value and the safety factor of the modified structure of the Landing Craft Tank (LCT) ship deck construction. The method used in this research is the finite element method. In this study uses 2 variations of the type of support